MAO Inhibitory Activity of 2‐Arylbenzofurans versus 3‐Arylcoumarins: Synthesis, in vitro Study, and Docking Calculations. Issue 6 (15th April 2013) - Ferino, Giulio; Cadoni, Enzo; Matos, Maria João; Quezada, Elias; Uriarte, Eugenio; Santana, Lourdes; Vilar, Santiago; Tatonetti, Nicholas P.; Yáñez, Matilde; Viña, Dolores; Picciau, Carmen; Serra, Silvia; et al.
Abstract Monoamine oxidase (MAO) is an important drug target for the treatment of neurological disorders. Several 3‐arylcoumarin derivatives were previously described as interesting selective MAO‐B inhibitors. Preserving the trans‐stilbene structure, a series of 2‐arylbenzofuran and corresponding 3‐arylcoumarin derivatives were synthesized and evaluated as inhibitors of both MAO isoforms, MAO‐A and MAO‐B. In general, both types of derivatives were found to be selective MAO‐B inhibitors, with IC50 values in the nano‐ to micromolar range. 5‐Nitro‐2‐(4‐methoxyphenyl)benzofuran (8) is the most active compound of the benzofuran series, presenting MAO‐B selectivity and reversible inhibition (IC50=140 nM). 3‐(4′‐Methoxyphenyl)‐6‐nitrocoumarin (15), with the same substitution pattern as that of compound 8, was found to be the most active MAO‐B inhibitor of the coumarin series (IC50=3 nM). However, 3‐phenylcoumarin 14 showed activity in the same range (IC50=6 nM), is reversible, and also severalfold more selective than compound 15. Docking experiments for the most active compounds into the MAO‐B and MAO‐A binding pockets highlighted different interactions between the derivative classes (2‐arylbenzofurans and 3‐arylcoumarins), and provided new information about the enzyme–inhibitor interaction and the potential therapeutic application of these scaffolds.